The Usage Of Bakamla Force In Safeguarding The Seas Of Indonesian Jurisdiction - Muh. Ilyansyah; Lukman Yudho Prakoso; Rudi Sutanto; Tasdik, Tasdik; Sri Patmi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This abstract aims to highlight Indonesia's maritime security challenges, including threats, jurisdictional defense, and Bakamla's role. It also discusses limitations in maritime operational capabilities. This study employs a qualitative research method to describe, explore, and understand the meaning perceived by individuals or groups regarding current social or human phenomena. The research adopts a juridical-normative approach with a focus on the principles of the use of force by Bakamla RI. Data is collected through literature reviews and analyzed using qualitative data analysis techniques proposed by Miles, Huberman, and Saldana (2014) which involve data condensation, data display, and conclusion drawing and verification. The result is maritime security is an important aspect for a country. Maritime security refers to threats to the maritime. The Indonesian Sea, which has abundant natural resource potential and as an international trade route, is vulnerable to maritime threats. The Maritime Security Agency or Bakamla exists as an effort to maintain and defend the jurisdiction of Indonesian waters for the sake of national interests. In its role, often the threat is faced with a situation in which the use of force must be carried out. The use of force is a last resort to address existing threats based on the basic principles of the use of force and firearms (BPUFF), codes of law enforcement, human rights and applicable national and international law.   The use of force must be carried out based on the scale and level of risk of the existing threat, not necessarily the use of force is allowed under the pretext of self-defense.The conclusion is Indonesia's maritime richness faces increasing threats, necessitating careful use of force by Bakamla, guided by legal and ethical considerations.